Performance and Dependability of structured peer-to-peer overlays - Castro, Miguel; Costa, Manuel; Rowstron, Ant (Proceedings of the International Conference on Dependable Systems and Networks (DSN-2004), 2004)
Structured peer-to-peer overlay networks provide a useful substrate for building distributed applications. They map object keys to overlay nodes and offer a primitive to send a message to the node responsible for a key. They can implement, for example, distributed hash tables and multicast trees. However, there are concerns about the performance and dependability of these overlays in realistic environments. Several studies have shown that current peer-to-peer environments have high churn rates: nodes join and leave the overlay continuously. This paper presents techniques that continuously detect faults and repair the overlay to achieve high dependability and good performance in realistic environments. The techniques are evaluated using large-scale network simulation experiments with fault injection guided by real traces of node arrivals and departures. The results show that previous concerns are unfounded; our techniques can achieve dependable routing in realistic environments with an average delay stretch below two and a maintenance overhead of less than half a message per second per node.